2016
DOI: 10.1021/acs.organomet.6b00161
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Catalyzed Borylation of Aryl Halides and Pseudohalides

Abstract: We report the first Co-catalyzed borylation of aryl halides and pseudohalides with bis­(pinacolato)­diboron (B2pin2). The synthesis of two new Co­(II) complexes of oxazolinylferrocenylphosphine ligands is described. Upon activation with LiMe, the Co complex catalyzes the borylation reactions of aryl bromides, iodides, sulfonates, arenediazonium salts, and even aryl chlorides under mild conditions, providing the borylated products in excellent to moderate yields and with high functional group tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 100 publications
1
16
0
Order By: Relevance
“…However, it must be considered that TEMPO might promote the decomposition of B 2 pin 2 . 30 Starting with para-iodotoluene, formation of toluene and a biphenyl derivative was later observed under these reaction conditions strongly supporting the presence of aryl radicals. 12 Since the aryl iodides applied by Wu and Zhang are not particularly activated for a nucleophilic substitution at the ipsocarbon atom, we suggest a radical chain reaction for this transformation (Scheme 6a).…”
Section: Dehalogenative Borylation (Sp 2 )mentioning
confidence: 82%
See 1 more Smart Citation
“…However, it must be considered that TEMPO might promote the decomposition of B 2 pin 2 . 30 Starting with para-iodotoluene, formation of toluene and a biphenyl derivative was later observed under these reaction conditions strongly supporting the presence of aryl radicals. 12 Since the aryl iodides applied by Wu and Zhang are not particularly activated for a nucleophilic substitution at the ipsocarbon atom, we suggest a radical chain reaction for this transformation (Scheme 6a).…”
Section: Dehalogenative Borylation (Sp 2 )mentioning
confidence: 82%
“…Even though the authors did not provide a clear mechanistic picture, a radical chain process that is initiated by ET from an intermediately generated Co I species is feasible. 30…”
Section: Aryl Halidesmentioning
confidence: 99%
“…35 Recent advances in the preparation of arylboronic acid derivatives revealed that these compounds can be generated by the borylation of aryl halides with diborons. 36−39 Several metal complexes, including Pd, 40−43 Rh, 44 Fe, 45 W, 46 Zn, 47−50 Co, 51,52 Cu, 53−56 and Ni, 57−60 have been proven to be able to catalyze the borylation of aryl halides. It is found that visible light 61,62 and free radicals 63,64 are also effective in this transformation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Arylboronic acid derivatives are highly valuable synthetic precursors that are widely used as intriguing building blocks in organic synthesis, particularly as substrates for transition-metal-catalyzed C–C, C–O, and C–N bond-forming reactions . Recent advances in the preparation of arylboronic acid derivatives revealed that these compounds can be generated by the borylation of aryl halides with diborons. Several metal complexes, including Pd, Rh, Fe, W, Zn, Co, , Cu, and Ni, have been proven to be able to catalyze the borylation of aryl halides. It is found that visible light , and free radicals , are also effective in this transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Using biaryl iodides or bromides as substrates, the reaction suffers from large quantities of hydrodehalogenation byproducts. A cobalt‐catalyzed borylation of aryl halides and pseudohalides, also including aryl chlorides, was reported utilizing expensive oxazolinylferrocenyl‐phosphine ligands and MeLi, a reactive organometallic reagent . Another milder method for the borylation of aryl chlorides, employing a Co II ‐NHC catalyst and KOMe as the base at 50 °C, was recently introduced by Geetharani and co‐workers .…”
Section: Introductionmentioning
confidence: 99%